Reconstruir la historia local: el archivo histórico y el museo de la localidad de Porteña - Fogliato, Silvana; Florián, Alicia (Res Gesta, 2018)
Mrs. Susana Pagliaro is in charge of the Municipal Historical Archive of the town of Porteña (Province of Cordoba), one of the oldest in the area, and which is part of the Network of Archives of the Northeast of Cordoba. Veronica Gorosito and Mariel Aimar, as well as Natalia Montivero, in charge of photography and digitalization, and Mayra Castaño, the person designated to requisition data, collaborate with the Archives. From the local Museum collaborates its director, the museologist Santiago Seeber. Through the aforementioned Network, an oral history archive has been built, which brings together a large number of testimonies from inhabitants of the region, and the donation of documentation and photographs has been promoted. In 1993 the Municipal Historical Archive of Porteña began to publish the magazine Abrojo, discontinued in 2003, and put back into circulation in 2012. This relaunch was related to the beginning of a research project on local history through existing sources in the city of Cordoba, which has the support of municipal authorities. As a result of the research carried out, contact was made with the city of Roldán and its historians, in search of studying the economic link that both localities had in the past, due to the common development of the dairy industry. The interview took place on July 19, 2018 in Roland, following a trip of Susana Pagliero and Veronica Gorosito to this city.